2022
DOI: 10.1007/s00170-022-08946-2
|View full text |Cite
|
Sign up to set email alerts
|

Lattice structures in stainless steel 17-4PH manufactured via selective laser melting (SLM) process: dimensional accuracy, satellites formation, compressive response and printing parameters optimization

Abstract: By the term, lattice structures are intended topologically ordered open-celled structures consisting of one or more repeating unit cells. Technological development and especially the growth of the additive manufacturing (AM) industry allows innovative structural design, including complex lattice structure. Selective laser melting (SLM) is an AM process that enables the manufacture of space filling structures. This work investigated the influence of the most important process parameter settings on lattices prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Depending on their topology, the lattice structures are classified as strut based, which are formed by the interconnection of truss-like struts at the nodes, and triply periodic minimal surface lattice structures, which are mathematically generated periodic surfaces [1,18,19]. Numerous strut-based lattice structures were investigated and reported in the literature, including body-centered cell (BCC), face-centered cell (FCC), rhombic, Kelvin, octet truss, and Pillar Octahedral (other name BCCZ) lattice structure topologies [2,12,13,18,[20][21][22][23][24][25][26][27][28]. It was found that by increasing the diameter of the strut, which leads to a higher relative density of the lattice structure, their mechanical properties and energy absorption increase, but it is to the detriment of its mass.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on their topology, the lattice structures are classified as strut based, which are formed by the interconnection of truss-like struts at the nodes, and triply periodic minimal surface lattice structures, which are mathematically generated periodic surfaces [1,18,19]. Numerous strut-based lattice structures were investigated and reported in the literature, including body-centered cell (BCC), face-centered cell (FCC), rhombic, Kelvin, octet truss, and Pillar Octahedral (other name BCCZ) lattice structure topologies [2,12,13,18,[20][21][22][23][24][25][26][27][28]. It was found that by increasing the diameter of the strut, which leads to a higher relative density of the lattice structure, their mechanical properties and energy absorption increase, but it is to the detriment of its mass.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complexity of the physical phenomena occurring in the SLM process, identifying the impact of parameters such as laser power, scan speed, scan strategy, hatch spacing, and material or powder particles on the surface integrity and the geometric accuracy of the manufacturing parts [5][6][7][8][9] is difficult. The research conducted on the optimization of the SLM process [10][11][12][13] improved the properties of the manufactured parts; however, achieving a roughness below 1 micron, which is very often required in industrial applications, is still a challenge. Despite the many advantages of using SLM in the production of parts for the aerospace or power industry [14,15], the high surface roughness, dimensional and geometric inaccuracy [16,17], defects of surface layers such as balling effect [18,19], power adhesion [20], and microcracks [21,22] in many cases require the use of additional post-processing technologies [23].…”
Section: Introductionmentioning
confidence: 99%
“…While SLM can be used to create metal lattice structures it represents certain difficulties like the need for supports for lattice structure struts. This is especially true for the horizontal struts [9,10]. In addition, the cost of the SLM process is high.…”
Section: Introductionmentioning
confidence: 99%